Associations of Sex Hormones and Hormonal Status With Arterial Stiffness in a Female Sample From Reproductive Years to Menopause - Laakkonen, Eija K.; Karppinen, Jari E.; Lehti, Satu; Lee, Earric; Pesonen, Emilia; Juppi, Hanna-Kaarina; Kujala, Urho M.; Haapala, Eero A.; Aukee, Pauliina; Laukkanen, Jari A.; Ihalainen, Johanna K. (Frontiers in Endocrinology, 2021)
Objective: Loss of sex hormones has been suggested to underlie menopause-associated increment in cardiovascular risk. We investigated associations of sex hormones with arterial stiffness in 19–58-years-old women. We also studied associations of specific hormonal stages, including natural menstrual cycle, cycle with combined oral contraceptives (COC) and menopausal status with or without hormone therapy (HT), with arterial stiffness. Methods: This study includes repeated measurements of 65 healthy women representing reproductive (n=16 natural, n=10 COC-users) and menopause (n=5 perimenopausal, n=26 postmenopausal, n=8 HT-users) stages. Arterial stiffness outcomes were aortic pulse wave velocity (PWVao) and augmentation index (AIx%) assessed using Arteriograph-device. Generalized estimating equation models were constructed to investigate associations of each hormone (wide age-range models) or hormonal stage (age-group focused models) with arterial stiffness. PWVao models with cross-sectional approach, were adjusted for age, relative fitness, fat mass and mean arterial pressure, while models with longitudinal approach were adjusted for mean arterial pressure. AIx% models used the same approach for adjustments and were also adjusted for heart rate. Results: Negative and positive associations with arterial stiffness variables were observed for estradiol and follicle-stimulating hormone, respectively, until adjustment for confounding effect of age. In naturally menstruating women, AIx% was higher at ovulation (B=3.63, p<0.001) compared to the early follicular phase. In COC-users, PWVao was lower during active (B=-0.33 - -0.57, p<0.05) than inactive pills. In menopausal women, HT-users had higher PWVao (B=1.43, p=0.03) than postmenopausal non-HT-users. Conclusions: When using wide age-range assessments covering reproductive to menopausal lifespan it is difficult to differentiate age- and hormone-mediated associations, because age-mediated influence on arterial stiffness seemed to overrule potential hormone-mediated influences. However, hormonal status associated differentially with arterial stiffness in age-group focused analyses. Thus, the role of sex hormones cannot be excluded. Further research is warranted to resolve potential hormone-mediated mechanisms affecting arterial elasticity.